2012
DOI: 10.1007/s00428-012-1296-x
|View full text |Cite
|
Sign up to set email alerts
|

A combination of smears and cell block preparations provides high diagnostic accuracy for endobronchial ultrasound-guided transbronchial needle aspiration

Abstract: Endobronchial ultrasound-guided transbronchial needle aspiration has demonstrated its accuracy in the diagnostic workup of enlarged mediastinal lymph nodes. In addition to conventional smears, the use of liquid-based cytology (LBC) and cell block preparations (CBP) has been introduced more recently. The aim of our study was to determine the performance of each of the different techniques, separately and combined, in terms of diagnostic yield and sensitivity. A total of 290 consecutive patients were included. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…The diagnostic yield of slide cytology and core-tissue are reported to be greater than 80% also in previous series (4,(6)(7)(8). In our study no significant differences were seen between the diagnostic performances comparing these two techniques.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The diagnostic yield of slide cytology and core-tissue are reported to be greater than 80% also in previous series (4,(6)(7)(8). In our study no significant differences were seen between the diagnostic performances comparing these two techniques.…”
Section: Discussionsupporting
confidence: 47%
“…Also in the literature the combination of two techniques, both slide cytology and cell-block or core tissue, are reported to increase the diagnostic performance of the same methods alone (4,(6)(7)(8). However, processing the specimen in two different ways at the same time requires more resources and raises the question of which method should be trusted in case of discordant results.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that a cell block is prepared in conjunction with LBP (reports for TP) this is particularly important because fluids may contain large fragments that may not pass through the filter and are only noticed on the CB [15]. Other reports echoed similar findings in transbronchial aspirates and washes [16][17][18]. This has also been the first author's experience especially in hemorrhagic effusions.…”
Section: Laboratory Processingmentioning
confidence: 85%
“…Similarly, Wallas et al [12], in their study of aspirates processed by TP, reported 1 case of noncaseating granulomata detected only on CB. In the study by Gauchotte et al [14], the sensitivity for detecting granulomata was 30% for smears, 4.5% for TriP and 82.8% for CB (fig. 4).…”
Section: Resultsmentioning
confidence: 98%
“…3a). In endoscopic ultrasound-guided transbronchial needle aspiration, Gauchotte et al [14] reported a sensitivity of 86.4% for TriP and 92.9% for CP of SmCC. Using residual material from 101 Sp samples evaluated for SmCC, Wu et al [15] reported a diagnostic sensitivity of 80.2% for TriP versus 63.4% for smears.…”
Section: Resultsmentioning
confidence: 99%